2022
DOI: 10.3171/2021.8.peds21281
|View full text |Cite
|
Sign up to set email alerts
|

Early posttraumatic seizures in pediatric traumatic brain injury: a multicenter analysis

Abstract: OBJECTIVE Early posttraumatic seizures (EPTSs) in children after traumatic brain injury (TBI) increase metabolic stress on the injured brain. The authors sought to study the demographic and radiographic predictors for EPTS, and to investigate the association between EPTS and death, and between EPTS and poor functional outcomes among children with moderate to severe TBI in Asia. METHODS A secondary analysis of a retrospective TBI cohort among participating centers of the Pediatric Acute & Critical Care Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Given that this is a single-center study, findings may not be generalizable across multiple centers, although we identified that characteristics of our EPTS patient cohort are consistent with those observed from other centers. [3][4][5] Cerebral regional oximetry may not adequately reflect changes in cerebral oxygenation or capture changes reflective of where seizures arose, although we attempted to mitigate against this by investigating probes ipsilateral to seizure onset, as well as performing subgroup analysis of patients with frontal lobe seizures. Intracranial pressure monitoring from an intraparenchymal probe may reflect changes in ICP at the probe site and may not necessarily reflect changes within ictal regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that this is a single-center study, findings may not be generalizable across multiple centers, although we identified that characteristics of our EPTS patient cohort are consistent with those observed from other centers. [3][4][5] Cerebral regional oximetry may not adequately reflect changes in cerebral oxygenation or capture changes reflective of where seizures arose, although we attempted to mitigate against this by investigating probes ipsilateral to seizure onset, as well as performing subgroup analysis of patients with frontal lobe seizures. Intracranial pressure monitoring from an intraparenchymal probe may reflect changes in ICP at the probe site and may not necessarily reflect changes within ictal regions.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings that EPTS were associated with younger ages and worsened outcomes is consistent with prior literature. 3 Heterogeneity between subjects of EPTS responses on systemic and cerebral physiology raises questions regarding the management to mitigate secondary brain injury. Effective management against EPTS may not need to be simplified into dichotomous decision making regarding whether to treat to seizures aggressively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation